Navigating Vocabulary Limitations: Conversation Control Strategies of Indonesian EFL University Students - Wulan Sefia; Girindra Putri Dewi Saraswati (Journal of English Language and Education, 2026)
Vocabulary limitation remains a major challenge in English as a Foreign Language (EFL) speaking, particularly in higher education contexts. However, few studies have explored how learners perceive their vocabulary limitations and how they manage them in real-time communication. This study aimed to investigate Indonesian EFL university students’ perceptions of vocabulary limitation and the conversation control strategies they employ. A descriptive qualitative design was used, involving 20 students through an open-ended questionnaire and follow-up interviews. The findings revealed that students perceived their vocabulary as sufficient for basic communication but limited in more complex contexts. Vocabulary limitation affected both speaking performance, leading to hesitation and simplification, and psychological factors such as anxiety and lack of confidence. To overcome these challenges, students employed various strategies, including paraphrasing, code-switching, using gestures, asking for help, and using fillers. These findings highlight the importance of integrating strategic competence into language teaching to support effective communication.